Method and apparatus for processing and filtering wastewater for removing solid waste and FOG (fats, oils and grease) from the wastewater - Mustapha, Faizal; Karjanto, Jufrizal; Md. Yusof, Nidzamuddin; Samsuddin, Rosnah; Abg Abdul Majid, Dayang Laila (2012)
An apparatus 100 for processing and filtering wastewater and removing solid waste and FOG (fats, oils and grease) from the wastewater, includes a housing 105 including an inlet port 3 for taking wastewater, and an outlet port 4 for discharging wastewater after removing the solid waste and the FOG, a first filter 1 positioned inside the housing 105 for filtering the wastewater, a deflector 7 mounted on a bottom surface of the housing 105 for slowing down wastewater flowing from the first filter 1 and retaining the wastewater to form at least one layer of the FOG, a FOG collector 8, 11 to collect the FOG from the wastewater by separating the at least one layer of the FOG and a plurality of vertical panels 9, 10 mounted inside the housing 105 for facilitating discharge of wastewater without the FOG through the outlet port 4 of the housing 105.